ISTIHSĀN, MENGAPA DITENTANG? (PRO-KONTRA KEHUJJAHAN ISTIHSĀN) - Halim, Ahmad Rasyidi (Nurani, 2017)
During the time of Imam Hanafi, there was a spreading of false hadiths, so he was very careful about it, so that when there is a case that is not found in the Qur'an or shahih hadith, one of the methods used is istihsān, unlike Imam Syafi 'i which in its time is increasingly widespread of personal groups and groups that refused against sunnah, so people when it prefers to use the mind rather than the nash, the social influence makes Imam Shafi'i harder in terms of purifying the primary teachings of Islam namely the Qur'an and sunnah, thus limiting the use of reason and reason, including the good presumption in deciding a case on the basis of reason and lust. This is the background why Imam Hanafi accepted istihsān and on the contrary Imam Shafi'i refused.